2018
DOI: 10.1007/s11769-018-0987-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short-term Forest Bathing in Urban Parks on Perceived Anxiety of Young-adults: A Pilot Study in Guiyang, Southwest China

Abstract: Forest can be taken as a natural therapy to alleviate perceived anxiety of visitors. Given the geographical difference between urban and rural forest environments, little is known about the urban forest therapy effect of anxiety alleviation with reference to the rural forest. In this study, forty-three university students (aged from 19 to 23) were recruited as participants to visit the forest parks at urban and rural areas of Guiyang City on 21 and 23 December 2016. The forest experience was separated by four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 43 publications
1
66
0
Order By: Relevance
“…Ranked data were tested by Friedman's chi-square test to detect the probability of different row-means in data tables stratified by variations from cities, urban-forest park locations, and their interactions. When a significant effect was found, data were arranged and compared by the Wilcoxon rank-sum test [46,47]. Bonferroni adjustment was employed to test for significance at the 0.05 level [48].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ranked data were tested by Friedman's chi-square test to detect the probability of different row-means in data tables stratified by variations from cities, urban-forest park locations, and their interactions. When a significant effect was found, data were arranged and compared by the Wilcoxon rank-sum test [46,47]. Bonferroni adjustment was employed to test for significance at the 0.05 level [48].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a restorative forest effect was characterized by groups of trees by Jiang et al, who found that men can perceive discomfort in response to heavy tree density while women do not realize this stress [51]. Thus, tree density in urban forest parks of China might be greater than a male prefers [8,46,47]. However, the current understanding about the restorative response and gender difference to the forest experience is still limited.…”
Section: The Gender Effect On Facial Expressionmentioning
confidence: 99%
“…In this study, a pre-test-post-test design was applied to one group. This design is frequently used to assess the effectuality of forest recreation programs [6,[8][9][10]. The current study did not have a control group, however, which might violate its internal validity.…”
Section: Experimental Limitationsmentioning
confidence: 97%
“…Physiological indices were also affected, as this program resulted in lowered diastolic blood pressure and pulse rate in the participants [7]. A two-day forest therapy program conducted in urban parks in China had an antianxiety effect [8], and another two-day forest therapy program conducted in a recreational forest in Taiwan had a significant positive influence on the mood states of women involved in the study, causing a decrease in both anxiety levels and systolic blood pressure [9]. A five-day forest therapy program conducted in Japan also had a positive influence on the mood states of the participants [10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that walking in a forest can alleviate stress caused by personal work or activities, and the decompression effect caused by different forest conditions also changes stress levels [12][13][14][15]. In addition, a forest can contribute to recovery from health conditions [16].…”
Section: Introductionmentioning
confidence: 99%